Don't take it personally, it's just a joke: The masculine media discourse of jokes and cartoons on the Cyprus issue - Aliefendioğlu, Hanife; Arslan, Yetin (Elsevier, 2011)
This paper analyses the portrayal of women and femininity as a humorous object in the print media of North Cyprus within the broad context of political discourse. We aim to demonstrate how particular discourses embedded within a patriarchal ideology in the media become apparent in jokes and cartoons relating to the Cyprus issue. We have identified two interconnected patterns in the cartoons and jokes in the print media: ‘femininity as a laughable subject’ and ‘Cyprus/the Cyprus issue represented as a woman’. We have studied our material through critical discourse analysis; in other words, we analyze the media through the lens of discourse. Discourse in the media constitutes a social world and is associated with a particular representation of certain social practices. Accordingly, we have examined the gendered character of the Cyprus issue via its social, political, and historical aspects.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1016/j.wsif.2010.08.002) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: WOMEN'S STUDIES; Discourse analysis; Mass media; Women; Femininity